Effect of Active Learning through the Heuristic Problem-Solving Approach on Students’ Achievement in Linear Programming - Wakhata, Robert; Mutarutinya, Védaste; Balimuttajjo, Sudi (The International Journal of Science, Mathematics and Technology Learning, 2022)
This study examined the effect of active learning through the heuristic problem-solving approach on students’ achievement in linear programming (LP). The participants were 608 eleventh-grade students from eight public and private secondary schools in central and eastern Uganda. Multistage cluster sampling was used to select participants. A mixed-method approach was used. Specifically, a pretest-posttest non-equivalent quasi-experimental design was adopted. Classroom observation and LP diagnostic tests constituted data collection tools. Eight secondary schools participated; four applied the problem-solving heuristic approach while the remaining four applied the usual conventional instructional approach. To overcome the effect of non-randomization, data were matched using propensity score matching (PSM), and the Difference in Difference (DID) estimand was used for analysis. The findings revealed that the problem-solving heuristic approach had a significant impact on students’ achievement in LP (DID = 15.40). Generally, although both groups (comparison vs treatment) appear to have improved their average scores (4% vs 20%), the paired sample t-test (t(607) = 18.41, p = .000), and the effect size (Cohen’s d = 0.65) showed that students from the treatment group exhibited proficiency in solving LP problems compared to their counterparts from the comparison group. Students from central Uganda performed better. Generally, the entire classroom observation of the treatment group revealed that students’ mathematization of LP problems, their conceptual and procedural knowledge, understanding, and application of requisite knowledge in solving novel non-routine LP and related problem contexts improved. The study recommends adopting the problem-solving heuristic approach in secondary school mathematics to enhance instruction and assessment.
Keywords: Equations; Heuristic Problem-Solving Approach; Inequalities; Linear Programming; Model Eliciting Activities